2016
DOI: 10.1002/jmri.25538
|View full text |Cite
|
Sign up to set email alerts
|

Brain morphology and cortical thickness variations in systemic lupus erythematosus patients: Differences among neurological, psychiatric, and nonneuropsychiatric manifestations

Abstract: 2 Technical Efficacy: Stage 3 J. MAGN. RESON. IMAGING 2017;46:150-158.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…Zivadinov et al [43] conducted multimodal neuroimaging studies on lupus patients and found that cortical atrophy was the most relevant measurement index for central nervous system involvement in SLE. Similar SBM studies for SLE also found that SLE patients have thinner cortical thickness in multiple brain regions [9,19,20,44]. Many previous studies [10,[45][46][47] have also verified the cerebral cortical atrophy in SLE patients by VBM and other different technical modalities; therefore, cortical thickness can be regarded as one of the imaging biomarkers for structural changes in SLE patients.…”
Section: Hc(n=88)supporting
confidence: 59%
See 3 more Smart Citations
“…Zivadinov et al [43] conducted multimodal neuroimaging studies on lupus patients and found that cortical atrophy was the most relevant measurement index for central nervous system involvement in SLE. Similar SBM studies for SLE also found that SLE patients have thinner cortical thickness in multiple brain regions [9,19,20,44]. Many previous studies [10,[45][46][47] have also verified the cerebral cortical atrophy in SLE patients by VBM and other different technical modalities; therefore, cortical thickness can be regarded as one of the imaging biomarkers for structural changes in SLE patients.…”
Section: Hc(n=88)supporting
confidence: 59%
“…There has been no previous study separately on the non-NPSLE subgroup of SLE. Some brain regions with thin cortex identified here are well reported, such as the left supramarginal gyrus of NPSLE is thinner than control groups [ 20 ], the left superior temporal gyrus of SLE patients with episodic memory deficit is thinner than control groups [ 19 ], and the left superior parietal cortex of NPSLE is thinner than non-NPSLE [ 9 ], but newer abnormal brain areas have been discovered for the first time. We consider that this perceived discrepancy can be explained by differences in study population and the use of brain anatomy atlas.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…However, different approaches were used, where we specifically evaluated the corpus callosum and the hippocampus with a semi-automated quantitative approach, whereas they assessed atrophy in general using a qualitative rating scale. 12 In the present study, the FreeSurfer software was used as this software is well suited for evaluating subcortical structures like the hippocampus and corpus callosum, 36,37 and it is the same method as used previously for measuring subcortical atrophy. 23…”
Section: Discussionmentioning
confidence: 99%